Pengaruh pertumbuhan ekonomi, rata-rata lama sekolah dan tingkat pengangguran terhadap tingkat kemiskinan di Provinsi Jambi - Nandita Putri Syabrina; Hardiani Hardiani; Candra Mustika (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2021)
This study aims to: 1) To analyze the conditions of economic growth, the average length of schooling, unemployment rate, the poverty rate in Jambi Province 2001-2018. 2) To analyze the effects of economic growth, the average length of schooling, and the unemployment rate on poverty levels in Jambi Province in the period 2001-2018. The research analysis tool uses multiple linear regression analysis tools. Based on the results of the simultaneous test that economic growth, the average length of schooling, and unemployment rate together have a significant effect on poverty levels in Jambi Province, while the partial test results say that the significant effect on poverty levels is the variable of economic growth and the average length of the school. Then the results of the determination test indicate that the level of poverty is influenced by the independent variables in this study that is equal to 60.7 percent. Keywords: Economic growth, Average length of school, Unemployment rate, Poverty rate